Book Review: High Stakes: Children, Testing, and Failure in American Schools - Jeffrey S. Beaudry (Journal of Research in Rural Education, 2003)
Two professors, leaving academia to work in one elementary school for one year. They went for a story, one to use in their undergraduate and graduate teaching, and quickly found a story that went beyond their imagination'. After serving as interim teachers for a year, they poured out a book, where they never expected to write one. The results tell of their immersion in a highly structured, under-funded school and their disappointment and recriminations about the effects of high-stakes testing. While the introduction and conclusion summarize the apparent problems of high-stakes testing, what lies between' is a faithfully written chronicle that reads like a stack of 100 neatly arranged postcards from the testing zone.